Mechanical and dielectric behavior of LDPE/Bi-1212 films - Alkan, Umit; Kilic, Mehmet; Karabul, Yasar; Ozdemir, Zeynep Guven (WALTER DE GRUYTER GMBH, 2020)
The present study deals with the improvement of the mechanical and dielectric properties of low-density polyethylene (LDPE) by incorporating BiSr2CaCu2O6.5 (coded as Bi-1212) ceramic powder. In this context, LDPE/Bi-1212 films with different ceramic weight contents were prepared by hot press technique. The ceramic reinforcing material was produced by a solid-state reaction technique. While the surface morphologies of the films were determined using a scanning electron microscope (SEM), the chemical structure analyses of the samples were performed by Fourier transform infrared (FTIR) spectroscopy. The mechanical performances of the specimens were evaluated by determining the tensile strength, Young's modulus, percentage strain at break, and energy at the break values obtained by stress-strain curves. The real and imaginary components of the complex permittivity, as well as the alternating current (ac) conductivities of the samples, were measured within in the frequency interval of 1 Hz-1 MHz between 293 K and 353 K. As a result of tensile properties analyses as well as the investigations of ac electrical parameters, it was revealed that the LDPE/1.0 wt.-% Bi-1212 composite has a promising potential in electronic applications due to its improved mechanical durability, charge storage ability and conductivity.
Keywords: Low-density polyethylene; ceramics; dielectric spectroscopy; tensile properties; capacitors; ELECTRICAL-PROPERTIES; COMPOSITES; Materials Science